1994
DOI: 10.1029/93jd02857
|View full text |Cite
|
Sign up to set email alerts
|

Space‐time structure and reasons of global, regional, and local variations of atmospheric electricity

Abstract: Results of ground‐based measurements of the atmospheric electricity parameters at the network of middle‐ and high‐latitude observatories are used for the investigation of the space‐time structure of regular and irregular variations of the atmospheric electricity of fair weather Regular diurnal variations contain a complex superposition of universal, local, and magnetic local time controlled variations. Amplitudes of these components depend on season, latitude, and height of an observatory above the sea level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 11 publications
2
21
0
1
Order By: Relevance
“…Only one work (Sheftel et al, 1994) previously reported on studies of E z variations during GLEs according to ground based measurements at midlati tudes. It was also reported (Nikiforova et al, 2005;Kleimenova et al, 2009) that negative E z disturbances were observed at midlatitudes during powerful mag netic storms, which was explained by electron precip itation into subauroral latitudes during a magneto spheric substorm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one work (Sheftel et al, 1994) previously reported on studies of E z variations during GLEs according to ground based measurements at midlati tudes. It was also reported (Nikiforova et al, 2005;Kleimenova et al, 2009) that negative E z disturbances were observed at midlatitudes during powerful mag netic storms, which was explained by electron precip itation into subauroral latitudes during a magneto spheric substorm.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of solar flares and cosmic rays in the atmospheric electric field were studied in a number of works (Moiseev et al, 1993;Markson, 1978;Olson et al, 1978;Reagan et al, 1983;Goldberg, 1984;Sheftel et al, 1994;Zadorozhny et al, 1994;Rycroft et al, 2000;Farrel and Desch, 2002). It was noted that precipitation of relativistic protons (E > 450 MeV), which are typical of powerful SCR events (e.g., ground level events, GLEs), can result in considerable varia tions in atmospheric electric properties.…”
Section: Introductionmentioning
confidence: 99%
“…The authors assumed that regular diurnal variations contain a complex superposition of universal, local and magnetic local time controlled variations. Sheftel et al (1994b) also found an atmospheric electric response to Forbush decreases in GCR. Moreover, they studied the space-time structure of the atmospheric electricity effects arising from different physical causes, generically described as geoeffective solar flares.…”
Section: Global Data Representativeness and Short-term Pg Variationsmentioning
confidence: 94%
“…In spite of the fact that atmospheric electric data are influenced by local effects, the previously mentioned results also hint at global effects modulating the atmospheric electric parameters on a short time scale. Sheftel et al (1994b) reported on results derived from surface measurements of atmospheric electric parameters at a network of middle-and high-latitude observatories. The authors assumed that regular diurnal variations contain a complex superposition of universal, local and magnetic local time controlled variations.…”
Section: Global Data Representativeness and Short-term Pg Variationsmentioning
confidence: 99%
“…Thus, efforts have been invested in the development of networks (Sheftel et al 1994;Popov et al 2008) and databases (Dolezalek 1992;Tammet 2009), which can provide atmospheric electricity data from different locations. The comparison of PG measurements from sites displaced at substantial distances could identify common variations, which are attributed to the global circuit in the absence of coincident local factors (Harrison 2004b).…”
Section: Introductionmentioning
confidence: 99%